Tuberculous pericarditis: Challenges and controversies in the modern era - Kyriakakis, Charles G. (SA Heart Journal, 2016)
Tuberculous pericarditis (TBP) continues to wreak havoc across Sub-Saharan Africa (SSA). Despite more than 5 decades of treatment and research into TBP, we are not much closer to alleviating the suffering and mortality associated with this extrapulmonary manifestation of tuberculosis (TB). In the era of modern cardiology, diseases of the pericardium do not receive the same amount of research attention and investment as what diseases of lifestyle do. Interventional techniques for their diagnosis and management do not extend much further than pericardiocentesis with appropriate laboratory investigations. They also do not provide the potential for the development and use of consumable equipment, or that of expensive drugs and, consequently, fi nancial investment into their research and development is not forthcoming. Diseases of the pericardium do, however, remain important within the discipline that we practice and TBP in particular deserves our continuous efforts and attention. It is unfortunate to acknowledge that we have not made much of an impact on this ancient foe over the last 50 odd years. Despite the World Health Organisation (WHO) declaring TB a global emergency in 1993, more than 20 years later we are not much better off. In 2013 an estimated 9 million people developed the disease and 1.5 million died from it.(1) TBP is predominantly a disease of SSA and it requires a solution from the very region which it torments.